Analysis of polymorphisms in BRCA1 and BRCA2 genes in a population sample of canines from Uruguay - Decuadro, Alicia; Llambi, Silvia; Benech, Alejandro; Gagliardi, Rosa (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
In non-ovariectomized female dogs, breast tumors are the most frequent neoplasms. There are several points where canine and human breast tumors have clinical and molecular similarities. BRCA1 and BRCA2 genes have been extensively studied in both species. Regarding dogs, alterations in BRCA1 and BRCA2 have been identified in the development of breast tumors in different breeds. In this work, it was proposed to study exons 22 and 23 of the BRCA1 gene and exons 11 and 27 of the BRCA2 gene, in female dogs. It was studied two groups of female dogs, with or without mammary tumors. Regarding the genetic study of 15 loci, six were polymorphic, all of them were singles nucleotides polymorphisms (SNPs), while the other nine were monomorphic. It was obtained a low allelic variability, but at the population level, the tumor group has greater variability than the control group. On the other hand, the different analyses of possible groupings were negative, and it was not possible to clearly define groups with the parameters it was used. The foregoing may be a consequence of numerous factors such as characteristics inherent to the populations studied, such as the size of both populations; the breeds studied; tumor diversity. As it was mentioned before, the genes studied in this work have been widely related to breast cancer, both in humans and in dogs. In the former, they have been highly implicated in hereditary tumors. In dogs, it do not have that information. In the present case, it was founded no relationship between each of the markers studied and the occurrence of mammary tumor between the problem group and the control group.